PEMANFAATAN ADOBE FLASH SEBAGAI DASAR PENGEMBANGAN BAHAN AJAR FISIKA : STUDI LITERATUR - DWITRI PILENDIA (Jurnal Tunas Pendidikan, 2020)
The purpose of this reseach is to explore development of learning material that has been developed by using Adobe Flash in physics learning. This article uses literature study method with study the result of research about using Adobe Flash in physics learning material from 2010-2020. Based on study show that In Indonesia, the most used software in physics learning material is Adobe Flash. Adobe Flash as a basic for make picture, animation and simulation before combining with the other software. Some of the learning material that used Adobe Flash like FlipBook, games, Mobile Learning and Interactive Multimedia Learning. Using Adobe Flash is proved that can give optimal result in physics learning process. It showed by increasing of students result and interesting in physics learning.